JUST VIOLENT INTERTEXTUAL AND DYSTOPIAN RECENT REINSCRIPTIONS OF MOTHER NATURE IN JAMES JOYCE’S ULYSSES AND DORIS LESSING’S THE FIFTH CHILD? - Ioana Zirra (University of Bucharest Review. Literary and Cultural Studies Series, 2012)
Procreation is the theme developed in the “Oxen of the Sun” episode of James Joyce’s Ulysses and in Doris Lessing’s dystopia The Fifth Child. The contexts to which this theme is applied are violent by literary and literal standards alike. They go down to basics to reveal irreconcilable oppositions and even horror on the primeval scene of procreation, where gender enmities and ghastly pathologies of the modern are ready to work havoc. But do all literary texts stop here? The interrogation in the title invites meditation about the literary uses of violence as observable in the differing generic repertoires of modernist and post-modernist species of fiction. After duly noticing that Mother Nature as a literary master-trope appears already exhausted in its providential meaning and violently twisted by twentieth century contentious re-writing, we compare Joyce’s and Lessing’s novelistic images. Procreation slandered becomes on the Joycean scene the pretext for postcreation: a witty proliferation of masterful male words. Procreation appropriated by a demonstration about natural and social pathology is developed parabolically in Doris Lessing’s dystopia. The comparison measures the distance between the aims and potentialities of the modernist imaginary and those of literary creation after the postmodern turn. To avoid simple answers, we make an incursion into twenty-first century poetry to find mere traces of the Mother Nature literary trope in the cryptical volume of Geoffrey Hill’s 2011 collection of poems Clavics.